The Effect of Service Quality and Employee Performance on Customer Satisfaction at Fashion By Belvia Stores - Lubis, Aulia Azmi; Marliyah, Marliyah; Harahap, Muhammad Ikhsan (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
The business world is currently in great demand by the wider community, considering that various types of products and services are in great demand by business people. One of the business worlds that has tough competition is the fashion business. This is because trends in the fashion industry change dynamically from time to time. This study aims to see how much influence service quality and employee performance have on customer satisfaction. The research method used in this research is a quantitative research using a probability sampling technique with a purposive sampling approach for sampling and also using the Slovin formula. Questionnaires will be distributed to Fashion by Belvia Shop customers with a total sample of 61 respondents. The results of this study are the effect of service quality (X1) on customer satisfaction as the Y variable. From the analysis, it is obtained that a significant value is 0.007 <0.05 so it can be concluded that customer satisfaction has a significant influence on customer satisfaction. The effect of employee performance (X2) on customer satisfaction as the Y variable from the analysis obtained a significant value of 0.000 <0.05 so it can be concluded that employee performance has a significant influence on customer satisfaction.